ANALISIS KEPUASAN MAHASISWA DENGAN PENDEKATAN KANO MODEL SERTA QUALITY FUNCTION DEPLOYMENT (QFD) UNTUK MENINGKATKAN PELAYANAN AKADEMIK UNIVERSITAS MA CHUNG - Agil Haykal (Ma Chung Press, 2017)
Indonesia’s education system encourage universities to improve quality, so those universities can creates students with high quality. In order to improve service quality, the university needs accurate methods, so the improvement of service quality will be effective and efficient. Kano Model is an instrument to analyze consumer satisfaction on product/service’s attributes. Quality Function Deployment (QFD) is a quality system usually used to fulfill customer’s needs and improve customer satisfaction. There are 20 university academic service’s attributes which are being tested in this research. Generally, those attributes are classified in three categories, 6 attributes are classified as indifference, 10 attributes are classified as attractive, and 4 attributes are classified as one- dimensional. If university academic service quality’s improvement is oriented on student’s satisfaction, so the attributes that do not affect satisfacton not necessarily to be improved. Ma Chung University could achieve significant student’s satisfaction by improving quality of curriculum, subject’s syllabus, teacher’s certification, teacher’s training, teacher’s title, and janitor.